2022
DOI: 10.3390/su14106372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak Risk Perception on Willingness to Consume Products from Restaurants: Mediation Effect of Risk Attitude

Abstract: The COVID-19 outbreak caused huge losses for the catering industry. The outbreak’s influence on consumers’ risk perception and risk attitude was an important factor for these heavy losses. The aim of this study was to investigate the change in epidemic risk perception, risk attitude, and the consumers’ willingness to consume products from restaurants during the spread of the COVID-19 epidemic. The study collected 502 questionnaires at the end of 2021, and structural analysis was conducted using SPSS 26.0 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Fourth, there is a significant mediating role of attitude between perceived emotional risk and behavioural intentions, which is consistent with the findings of Zhao Li, Wangbing Liang et al [105]. Individuals with perceived emotional risk during the ongoing COVID-19 epidemic have increased positive attitudes towards forest therapy tourism, leading to more behavioural intentions.…”
Section: Discussionsupporting
confidence: 87%
“…Fourth, there is a significant mediating role of attitude between perceived emotional risk and behavioural intentions, which is consistent with the findings of Zhao Li, Wangbing Liang et al [105]. Individuals with perceived emotional risk during the ongoing COVID-19 epidemic have increased positive attitudes towards forest therapy tourism, leading to more behavioural intentions.…”
Section: Discussionsupporting
confidence: 87%
“…This study complements the research results between risk perception of COVID-19 and livelihood strategy change intention as one of the subjective factors of the object, and is also a response to the necessity of dynamically and quantitatively considering the impact of livelihood strategy change from other subjective factors outside the sustainable livelihood framework pointed out by Sun et al (2020) [13]. This conclusion to some extent supports Li's (2022) conclusion that risk perception of COVID-19 has a significant impact on consumers' willingness to consume products from restaurants [52], and Zhao's (2022) conclusion that risk perception of COVID-19 significantly and positively predicts individuals' hoarding behavior [17]. It provides a theoretical explanation for the willingness of tourism practitioners in ethnic communities to change their livelihood strategies with tourism as the main livelihood strategy.…”
Section: Theoretical Implicationssupporting
confidence: 57%
“…In the last two years, China entered the post-pandemic era, which means that the COVID-19 pandemic is largely under control in China, but has not subsided and may break out in a small scale or even large-scale event at any time [1][2][3]. However, studies have shown that COVID-19 has triggered a wide range of travel fears [4][5][6][7][8]. Moreover, the continuous variation and mutation of COVID-19 reflects its capricious nature, with the internet being flooded with mass amounts of false information about the COVID-19 pandemic [9][10][11], which may also lead people to panic, fear, or hesitation to travel.…”
Section: Introductionmentioning
confidence: 99%